2019
DOI: 10.15252/embj.2019102578
|View full text |Cite|
|
Sign up to set email alerts
|

Phosphoproteomics reveals conserved exercise‐stimulated signaling and AMPK regulation of store‐operated calcium entry

Abstract: Exercise stimulates cellular and physiological adaptations that are associated with widespread health benefits. To uncover conserved protein phosphorylation events underlying this adaptive response, we performed mass spectrometry‐based phosphoproteomic analyses of skeletal muscle from two widely used rodent models: treadmill running in mice and in situ muscle contraction in rats. We overlaid these phosphoproteomic signatures with cycling in humans to identify common cross‐species phosphosite responses, as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 115 publications
(144 reference statements)
3
63
0
Order By: Relevance
“…A very recent study suggests that the STIM2 plays a specific role in recruiting CAMKK2 to AMPK (Chauhan et al, 2019), so future studies to examine the temporal regulation of STIM1/2 and CAMKK2 localization and phosphorylation following metformin treatment in hepatocytes is warranted. While this manuscript was in revision, a phospho-proteomics of exercise across species identified Ser257 and Ser521 of STIM1 as being induced by AMPK in all contexts and further detailed their roles in SOCE (Nelson et al, 2019). Future comparisons of the phospho-proteomics of response to exercise versus metformin may reveal additional interesting common nodes between these two broadly beneficial interventions.…”
Section: Discussionmentioning
confidence: 89%
“…A very recent study suggests that the STIM2 plays a specific role in recruiting CAMKK2 to AMPK (Chauhan et al, 2019), so future studies to examine the temporal regulation of STIM1/2 and CAMKK2 localization and phosphorylation following metformin treatment in hepatocytes is warranted. While this manuscript was in revision, a phospho-proteomics of exercise across species identified Ser257 and Ser521 of STIM1 as being induced by AMPK in all contexts and further detailed their roles in SOCE (Nelson et al, 2019). Future comparisons of the phospho-proteomics of response to exercise versus metformin may reveal additional interesting common nodes between these two broadly beneficial interventions.…”
Section: Discussionmentioning
confidence: 89%
“…One protein whose phosphorylation was conserved in response to exercise was STIM1. Moreover, the authors demonstrated that STIM1 phosphorylation in response to exercise negatively regulates SOCE (Nelson et al 2019). This is contradictory to the idea of SOCE as a SR refiller to prevent fatigue during exercise.…”
Section: Physiological Significance Of Soce In Skeletal Musclementioning
confidence: 79%
“…We also point out that the SOCE mechanism and kinetics in muscle is not different between slow-and fast-twitch fibres (Cully et al 2016), thus making it unlikely that a role of SOCE is based around fatigue-resistance. Ivarsson et al (2019) and Nelson et al (2019) have recently reported enlightening results around the role of SOCE signalling in muscle. Nelson et al described a set of conserved phosphorylation events in mouse, rat and human in response to exercise.…”
Section: Physiological Significance Of Soce In Skeletal Musclementioning
confidence: 99%
“…Incubation at 1.5% O 2 up-regulated activities of LKB1 in MEFs [ 155 ], and CaMKK2 in 143B osteosarcoma cells associated with Ca 2+ influx and relocation of stromal interaction molecule 1- (STIM1) to the plasma membrane [ 156 ]. Intriguingly, STIM1 was identified as an AMPK substrate in L6 myotubes and validated in AMPK β1/β2 knockout MEFs, with two AMPK sites phosphorylated in both contracted rat and exercised mouse skeletal muscle [ 10 ]. Phosphorylation at STIM1-S257 was associated with altered STIM1 conformation and decreased store-operated Ca 2+ entry, hinting at negative feedback regulating AMPK signalling during exercise.…”
Section: Other Ampk Modifications (Non-phosphorylation)mentioning
confidence: 99%
“…Central to the propagation of these exercise-induced signalling events is the activity of AMP-activated protein kinase (AMPK), the energy guardian or metabolic “fuel gauge” of the cell [ 9 , 10 , 11 , 12 ]. As a whole, AMPK upregulates catabolic, nutrient/ATP-generating processes such as fat oxidation, glucose uptake and autophagy, while restraining anabolic, ATP-consuming processes such as protein and lipid synthesis.…”
Section: Introductionmentioning
confidence: 99%